2014
DOI: 10.1007/s10014-013-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system Epstein–Barr virus-positive diffuse large B-cell lymphoma of the elderly: a clinicopathologic study of five cases

Abstract: We report five cases of primary central nervous system (CNS) Epstein-Barr virus (EBV)-positive lymphoma of the elderly. This represented an incidence of 4 % of primary CNS diffuse large B-cell lymphoma (DLBCL) after EBV screening in 134 cases. All five patients were 65 years or older with no previous history of congenital or iatrogenic immune deficiencies. The histologic morphology of all the cases was DLBCL, with variable amounts of necrosis. The cell of origin (COO) as determined by the Hans algorithm disclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The proportion of positivity for most biomarkers in this study was similar to that in previous studies [11,[29][30][31]. The positivity rate of Epstein-Barr virus was also similar to previously reported Asian data (9 % in Korea and 6.1-11.4 % in Japan) [32][33][34], and slightly higher than those of western countries (4 % in PCNSL of the elderly) [35]. Of all these biomarkers, no one was significantly associated with the intraocular involvement of PCNSL except Ki-67.…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of positivity for most biomarkers in this study was similar to that in previous studies [11,[29][30][31]. The positivity rate of Epstein-Barr virus was also similar to previously reported Asian data (9 % in Korea and 6.1-11.4 % in Japan) [32][33][34], and slightly higher than those of western countries (4 % in PCNSL of the elderly) [35]. Of all these biomarkers, no one was significantly associated with the intraocular involvement of PCNSL except Ki-67.…”
Section: Discussionsupporting
confidence: 93%
“…However, in a review of the reported cases, EBV‐positive diffuse large B‐cell lymphomas of the elderly did occur in the CNS of immunocompetent patients, arising in elderly patients aged > 50 years without predisposing immunodeficiencies, suggesting that this disease in the CNS also has a relationship with an immunological deterioration derived from the aging process. Therefore, taking into consideration additional common clinicopathological features, several investigators have recently considered that EBV presence in primary CNS B‐cell lymphomas in immunocompetent elderly patients should be categorized with primary CNS EBV‐positive diffuse large B‐cell lymphomas of the elderly (Table ) …”
Section: Primary Cns Ebv‐positive Diffuse Large B‐cell Lymphomas Of Tmentioning
confidence: 99%
“…Recent advances in investigation of primary CNS lymphomas and related diseases have provided clinicians and pathologists with new information about these diseases . Although primary diffuse large B‐cell lymphomas are designated as primary CNS lymphomas according to the WHO Classification of Tumours of Haematopoietic and Lymphoid Tissue, a variety of other CNS lymphomas, such as primary CNS Burkitt lymphoma, primary CNS B‐cell lymphomas that have features intermediate between diffuse large B‐cell lymphomas and Burkitt lymphoma, and primary CNS EBV‐positive diffuse large B‐cell lymphoma of the elderly, have been reported in recent years. In addition, there has been controversy regarding cases of primary CNS lymphoid granulomatosis …”
Section: Introductionmentioning
confidence: 99%
“…Risk factors in immunocompetent patients are unknown, but long term immunosuppressive therapy or an underlying disease with associated immunosuppression are significant risk factors 7 . Lymphomagenesis is thought to be promoted by sustained antigenic stimulation by autoimmune diseases (such as SLE, Sjögren´s syndrome or rheumatoid arthritis) and/or by direct transforming properties of infectious agents 2,8,9 . CNS lymphomas developing in immunocompromised individuals are typically B-cell neoplasms, mostly DLBCL, and are EBV-positive (>95% vs 0%-20% in immunocompetent patients) 3,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomagenesis is thought to be promoted by sustained antigenic stimulation by autoimmune diseases (such as SLE, Sjögren´s syndrome or rheumatoid arthritis) and/or by direct transforming properties of infectious agents 2,8,9 . CNS lymphomas developing in immunocompromised individuals are typically B-cell neoplasms, mostly DLBCL, and are EBV-positive (>95% vs 0%-20% in immunocompetent patients) 3,9 . As in most CNS lymphomas developing in immunocompromised individuals, this patient was diagnosed with a DLBCL, and was EBV-positive.…”
Section: Discussionmentioning
confidence: 99%